Comparisons of some Andean Butterfly Faunas - Hovanitz, William (Caldasia, 1945)
Observations of the butterfly fauna at significant points along the top of the Andean mountain chain from near Venezuela in Colombia to central Ecuador in comparable ecologic niches has brought out some interesting facts concerning the sub-ecological prererences of the species and their mtercombination in building up the fauna of a particular region.